Eksistensi Kebudayaan Jawa dalam Penafsiran KH. Bisri Mustafa - al Hamid, Idrus (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2019)
Culture has a significant influence on the interpretation of the Qur’an. The influence has somehow integrated into the process of interpretation, which often colors the patterns of it. One of the Qur’anic exegeses which identity lies in Javanese culture is tafsir Al-Ibri?z. Besides a vernacular attempt, which signifies its main characteristic of interpretation, the color of Javanese culture is also an interesting topic to study. It is because the content of Javanese culture has been inherent in every single verse explained in various forms and ways. This study argues that Al-Ibri?z accommodates the values of Javanese culture as a mode of interpretation of the Qur’an. Those values lay in the basic principles of harmony and respect, which are part of the local Javanese ethics, the value of the concept of kerajawian (tradition applied in Jawa) about kawula pangeran (relationship between human and god) relation, and the imaginative-projective nature of Javanese thought.